ACEF and clinical SYNTAX score in the risk stratification of patients with heavily calcified coronary stenosis undergoing rotational atherectomy with stent implantation. Issue 7 (29th January 2014) - Pyxaras, Stylianos A.; Mangiacapra, Fabio; Wijns, William; Di Serafino, Luigi; De Vroey, Frederic; Toth, Gabor; Sinagra, Gianfranco; De Bruyne, Bernard; Heyndrickx, Guy R.; Barbato, Emanuele
<x xml:space="preserve">Abstract</x> Aim To assess ACEF (age, creatinine, and ejection fraction) and Clinical SYNTAX (CSS) score in the risk stratification of patients with heavily calcified stenosis undergoing rotational atherectomy with stent implantation (rota‐stenting). Methods and Results. ACEF and CSS were calculated in 221 consecutive patients with stable angina undergoing rota‐stenting. Mean age of the patients was 74 ± 10 years, left ventricular ejection fraction was 61 ± 18%, and final burr size 1.78 ± 0.24 mm, with 2.6 ± 0.9 burrs used for each patient. Primary end‐point was MACE at one‐year defined as the composite of cardiac death, myocardial infarction, and target vessel revascularization. Post‐hoc analysis was performed by stratifying the clinical outcome according to ACEF and CSS tertiles. At 1 year there was a significantly higher MACE rate in the high tertile of ACEF (24% for ACEFHigh vs. 13% for ACEFMid vs. 9% for ACEFLow; P = 0.017) and CSS (25% for CSSHigh vs. 12% for CSSMid vs. 8% for CSSLow; P = 0.008). The predictive accuracy for both ACEF and CSS was moderate (c‐statistics, 0.629 and 0.638, respectively). Conclusion Both ACEF and CSS predict with moderate accuracy MACE at 1‐year in patients with heavily calcified coronary stenosis undergoing rotational atherectomy with stent implantation. © 2014 Wiley Periodicals, Inc.